Study on Defensive Security Concepts and Policies - United Nations Office for Disarmament Affairs (United Nations, 1993)
Focusing on the military dimension, this study explores whether defensive security concepts and policies might be one way in which to address existing and emerging threats and risks while at the same time, strengthening the positive developments of recent years.